Friday

February 27, 2015

February 27, 2015

Posted by **Jeremy** on Monday, September 5, 2011 at 6:02pm.

- geometry -
**Mgraph**, Monday, September 5, 2011 at 7:26pmLet R(x1,y1), S(x2,y2), then

x1=(2*2+8)/3=4, y1=(2*3+(-9))/3=-1

x2=(2+2*8)/3=6, y2=(3+2*(-9))/3=-5

**Answer this Question**

**Related Questions**

Geometry-PLEASE CHECK ANSWERS! - In isosceles triangle DEF, DE=DF. Which of the ...

Geometry - Yes, I'm this desperate. I just have problems with coming up with the...

Geometry - Geometric Proofs.... Write a justification for each step Given: AB = ...

Geometric Proofs - Given: line AB is congruent to line AC, Angle BAD is ...

Geometric Proofs - Given: line AB is congruent to line AC, Angle BAD is ...

Math - Geometric Proofs.... Write a justification for each step Given: AB = EF, ...

math - ok i have another question.. in the square qrst and line qt is congruent ...

geometry - E And C are mid points od line AD and line DB; line AD is congruent ...

geometry - E And C are mid points od line AD and line DB; line AD is congruent ...

geometry - E And C are mid points od line AD and line DB; line AD is congruent ...